2009
DOI: 10.1590/s0100-204x2009000800026
|View full text |Cite
|
Sign up to set email alerts
|

Is tagging with visual implant elastomer a reliable technique for marking earthworms?

Abstract: -Visual implant elastomer (VIE) has recently been employed to investigate different aspects of earthworm ecology. However, a number of fundamental questions relating to the detection and positioning of the tag, its persistence and potential effects on earthworms remain unknown. Seven earthworm species belonging to three ecological groupings, with different pigmentation and burrowing behaviour, were tagged using different coloured VIE. External inspection after two days, one week and 1, 10 and 27 months were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Originally, VIE was developed for tagging salmon and other fish species (Northwest Marine Technology Inc., ). Today it is used with a variety of animal species (scorpions: Chapin, ; Ambystoma talpoideum : Doyle & Whiteman, ; slugs: Wallin & Latty, ; turtles: Davy, Coombes, Whitear, & MacKenzie, ; crayfish: Pilotto et al., ; snakes: Hutchens, Deperno, Matthews, Pollock, & Woodward, ; lizards: Waudby & Petit, ; earthworms: Butt, Briones, & Lowe, ). Even very small individuals such as trout alevins can be tagged with this system (Jensen, Hansen, & Thomassen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Originally, VIE was developed for tagging salmon and other fish species (Northwest Marine Technology Inc., ). Today it is used with a variety of animal species (scorpions: Chapin, ; Ambystoma talpoideum : Doyle & Whiteman, ; slugs: Wallin & Latty, ; turtles: Davy, Coombes, Whitear, & MacKenzie, ; crayfish: Pilotto et al., ; snakes: Hutchens, Deperno, Matthews, Pollock, & Woodward, ; lizards: Waudby & Petit, ; earthworms: Butt, Briones, & Lowe, ). Even very small individuals such as trout alevins can be tagged with this system (Jensen, Hansen, & Thomassen, ).…”
Section: Introductionmentioning
confidence: 99%
“…They are visible through the skin of the animals, particularly with a UV light. The tags are well supported by earthworms (Butt et al, 2009). They can stay up to months in their body, which is much longer than the previously mentioned tags (Butt et al, 2009).…”
Section: Figurementioning
confidence: 87%
“…Recent work [45] has shown that it is possible, through injection of Visual Implant Elastomer (VIE), available from Northwest Marine Technology [46] to visually colour tag earthworms. In addition these tags have been shown to be retained in a number of earthworm species for more than 2 years and have no detrimental effects on growth to maturity, mating, and cocoon production in one closely studied species, L. terrestris [47]. This technique 7 may well prove to be valuable in earthworm age determination but may also reveal much from studies of population dynamics, in terms of capture, mark recapture exercises.…”
Section: Life History Studiesmentioning
confidence: 98%